ANALISIS KORELASI FAKTOR KOMUNIKASI PROYEK TERHADAP PENCAPAIAN KINERJA WAKTU DI KOTA BANDA ACEH - Richard Mareno; Cut Zukhrina Oktaviani; Saiful Husin (Prodi Magister Teknik Sipil Unsyiah, 2022)
A communications project is the key to success in managing work. Poor communication can lead to a project success rate of only 52%, whereas with good communication the project success rate can reach 80%. The purpose of this study is to analyze the relationship of project communication factors to time performance achievement in Banda Aceh. Respondents in this study were project managers from contractor companies in Banda Aceh. Data processing techniques are carried out by correlation analysis. Based on the results of the data research showed the project communication factors have a very high relationship to time performance achievement. Performance reports, facilities and technology used, information delivery, communication skills, and coordination relationships partially have a very high relationship with Pearson coefficients of 0.823; 0.837; 0.940; 0.864, and 0.879. In this case, the 5 communication factors reviewed, all of them have a significant relationship with the value of Sig. 0.000 0.05 and simultaneously has a very high relationship of 98.4% to time performance achievement in Banda Aceh.